The moderating effects of national culture on the development of organizational learning culture: A multilevel study across seven countries - Miha Škerlavaj; Chunke Su; Meikuan Huang (Journal for East European Management Studies, 2013)
This study examines the moderating effects of national culture dimensions (Hofstede 1980) on three key elements in the development of organisational learning culture: information acquisition, information interpretation and behavioral and cognitive changes. Data were collected from 1333 companies in three CEE countries (Slovenia, Croatia, Macedonia) and other regions. The results showed that four national cultural dimensions (power distance, individualism, masculinity, and uncertainty avoidance) had no significant moderating effects on the relationship between information acquisition and information interpretation. However, the relationship between information interpretation and behavioral and cognitive changes was positively moderated by power distance, and negatively moderat ed by individualism, masculinity and uncertainty avoidance. – – Diese Studie untersucht die moderierende Wirkung der nationalen Kultur- Dimensionen (Hofstede 1980) auf drei wesentliche Elemente in der Entwicklung von organisationaler Lernkultur: Informationsbeschaffung, Informationsinter- pretation und sowie kognitiver und Verhaltens-Veränderungen. Die Daten wurden von 1333 Unternehmen in drei MOE-Ländern (Slowenien, Kroatien, Mazedonien) und anderen Regionen erhoben. Die Ergebnisse zeigten, dass vier nationale kulturelle Dimensionen (Machtdistanz, Individualismus, Männlichkeit und Unsicherheitsvermeidung) keine signifikanten Auswirkungen auf die Beziehung zwischen Informationsbeschaffung und Informationsnterpretation hatten. Allerdings wurde die Beziehung zwischen Informationinterpretation und kognitiven und Verhaltens-Veränderungen positiv durch Machtdistanz und negativ durch Individualismus, Maskulinität und Unsicherheitsvermeidung moderiert.
Keywords: 650; organisational lear ning; national culture; information acquisition; information interpretation; behavioral and cognitive changes.; Lernende Organisation; Unternehmenskultur; Nationalkultur; Informationsverhalten; Informationsversorgung; Slowenien; Kroatien; Mazedonien